Fenomenology Study; Traditional Care Urolithiasis in Wakuru Distric Sulawesi Tenggara - Fitriani Fitriani (Jurnal Kesehatan Pasak Bumi Kalimantan, 2021)
Urolithiaisis is one of the main diseases of the urinary tract. In the world this disease is included in the three most common diseases in the field of Urology. The incidence of urolithiasis in Wakuru village is high. The phenomenon in Wakuru Village is that most Urolithiasis patients prefer traditional medicine such as drinking herbal medicine from the cat's whiskers plant. This study aims to explore and understand in depth the phenomenon of traditional treatment of urolithiasis patients in Wakuru village. The design used qualitative descriptive phenomenology. Research participants were taken by purposive sampling, data interpretation using content analysis. the process of data collection was carried out by in-depth interviews. The results showed that there were two themes: the use of herbal keji beling for the treatment of urolithiais, the use of the kumis kucing plant for the treatment of urolithiasis. Increasing public knowledge and awareness in herbal treatments in utilizing herbal plants in the surrounding environment.Keywords : Traditional Care, Urolithiasis, Fenomenology Study